A framework for the Saudi universities governance to achieve competitive advantage in decision making according to the aspirations of Vision 2030 - Alqahtani, Reem Thabet Mohammad Bny Zeed (Journal of Educational and Psychological Sciences, 2019)
The research aimed at identifying the level of applying the governance decisions at the Imam Muhammad bin Saud Islamic University to achieve the competitive advantage in making decisions the decisions under the vision of the Kingdom 2030, identifying the requirements of its application and identifying the level of achievement of competitive advantage at the University of Imam Muhammad bin Saud Islamic under the vision of the Kingdom 2030. The research is based on the analytical descriptive approach. The study’s society is composed of all administrative and academic leaderships at the Imam Muhammad bin Saud Islamic University in the Kingdom of Saudi Arabia. The sample was limited to 63 people. The questionnaire consisted of three axes (the governance of Imam Muhammad bin Saud Islamic University, the requirements of applying governance at Imam Muhammad bin Saud Islamic University, and the level of availability of competitive advantage in decision making at the Imam Muhammad bin Saud Islamic University) in light of the vision of the Kingdom of 2030. The results of the study were as follows: the relative weights of the respondents’ responses ranged from (61.9%- 79.4%), and the total score of their responses on this axis was 74.2%. The relative weights of the responses of the sample respondents ranged on the second axis: the requirements for applying governance at the Imam Muhammad bin Saud Islamic University in the light of the Kingdom’s Vision 2030 ranged from 65.4% to 82.2%, the total score for their responses on this axis was 76.4%, and the relative weights of the responses of the sample respondents ranged on the third axis: the level of availability of the competitive advantage in decision- making at Imam Muhammad bin Saud Islamic University in view of the Kingdom’s Vision 2030 ranged from 60.6% to 76.8%, and the total score of their responses on this axis was 69.5%. In the light of the previous results, the study recommended the need to adopt the governance of universities as an administrative system in all Saudi and Arab universities, and provide all the necessary requirements for their application.